How ageing shapes body and space representations: A comparison study between healthy young and older adults. (March 2021) - Sorrentino, Giuliana; Franza, Matteo; Zuber, Charlène; Blanke, Olaf; Serino, Andrea; Bassolino, Michela
Abstract: To efficiently interact with the external world, the brain needs to represent the size of the involved body parts - body representations (BR) - and the space around the body in which the interactions with the environment take place - peripersonal space representation (PPS). BR and PPS are both highly flexible, being updated by the continuous flow of sensorimotor signals between the brain and the body, as observed for example after tool-use or immobilization. The progressive decline of sensorimotor abilities typically described in ageing could thus influence BR and PPS representations in the older adults. To explore this hypothesis, we compared BR and PPS in healthy young and older participants. By focusing on the upper limb, we adapted tasks previously used to evaluate BR and PPS plasticity, i.e., the body-landmarks localization task and audio-tactile interaction task, together with a new task targeting explicit BR (avatar adjustment task, AAT). Results show significantly higher distortions in the older rather than young participants in the perceived metric characteristic of the upper limbs. We found significant modifications in the implicit BR of the global shape (length and width) of both upper limbs, together with an underestimation in the arm length. Similar effects were also observed in the AAT task. Finally, both young and older adults showed equivalent multisensory facilitation in the space close to the hand, suggesting an intact PPS representation. Together, these findings demonstrated significant alterations of implicit and explicit BR in the older participants, probably associated with a less efficient contribution of bodily information typically subjected to age-related decline, whereas the comparable PPS representation in both groups could be supported by preserved multisensory abilities in older participants. These results provide novel empirical insight on how multiple representations of the body in space, subserving actions and perception, are shaped by the normal course of life.